MENIMBANG KATA-KATA (MENURUT TEORI KONVERGENSI SIMBOLIK ERNEST BORMANN) - Dewi, Yuni Retna (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2008)
Because the work of socials cientists and interpreters is so different, they often have trouble understanding and valuing their counterparts scholarship. This workplace tension parallels the struggle between ranchers and farmers in Rodgers and Hammersteins Broadway musical Oklahoma! One song calls for understanding and cooperation :The farmer and the cowman should be friends,Oh, the farmer and the cowman should be friends,One man likes to push a plough, The other likes to chase a cow,But thats no reason why they cant be friends.Â The problem, of course, is that farmers and ranchers want to push a plough or chase a cow over the same piece of land. Daily disputes over fences, water, and that are common between objective and interpretive scholars. Differences in ways of knowinq. views of human nature, values, goals of theory building, and methods of research seem to ensure tension and misunderstanding.Friendly attitudes between empiricists and critical interpreters are particularly hard to come by when each group insists on applying its own standards of judgment to the work of the other group. As a first-time reader of communication theory, you could easily get sucked in to making the same mistake. If youve had training in the scientific method and judged value of every communication theory by whether it predicts human behavior, youll automatically reject 50 percent of the theories presented in this book. On the other hand, if youâve been stepped in the humanities and expect every theory to help unmask the meaing of a text, youâll easily dismissed the other half.